Influence of Polishing Methods on the Bonding Effectiveness and Durability of Different Resin Cements to Dentin. (28th February 2018) - Ren, Lingyan; Li, Mingfei; Pan, Yahui; Meng, Xiangfeng
Abstract : The purpose of this study was to investigate the impact of polishing methods on the bonding effectiveness and durability of different resin cements to dentin. The dentin surfaces were either treated with a fine-grit diamond bur (polishing A) or further polished by polishing disks (polishing B), and then they were bonded with any one of the three resin cements, namely, etch-and-rinse, self-etch, and self-adhesive resin cements. After 24-hour or 2-year water storage, a microtensile bond strength ( μ TBS) test was performed. A scanning electron microscope (SEM) was used to observe the morphology of the smear layer as well as the resin-dentin bonding interface. The results indicated that a thinner smear layer thickness was created by polishing B compared with polishing A. Although self-etch and self-adhesive resin cements achieved a relatively high primary bond strength before water degradation, etch-and-rinse resin cement obtained a stable bond strength during water degradation. The application of an additional polishing procedure could improve the bond strength of self-etch and self-adhesive resin cements.